PENERAPAN METODE CROSS SELLING DAN UPSELLING PADA APLIKASI WEB E-COMMERCE - Rizal Amegia Saputra (Universitas Bina Sarana Informatika Kota Sukabumi, 2015)
Currently e-commerce has become a concept that is influential in the business world, many companies that offer merchandise at the website and for some communities in ecommerce is one of the solutions in the shop, because prospective buyers do not need to come to a place to buy goods. Stores On Computers are firms engaged in computer sales, this store has introduced a system of online sales, but not using a recommendation system on its website. The consumers who do not know how to choose a suitable computer according to the needs and which products are much in demand by other consumers. Lack of recommendation goods and the lack of facilities which products are most in demand, hence resulting in less than optimal sales. In this study applying the method of up-selling and cross-selling on the application to optimize sales.